Peculiarities of changes in endogenous intoxication indicators in the dynamics of the experimental periodontitis development - P. Olekshij; M. Regeda (Kazimierz Wielki University, 2023)
The aim of our work was to investigate the peculiarities of changes in endogenous intoxication rates: medium mass molecules (MMM) and erythrocyte intoxication index (EII) in the blood of guinea pigs in the experimental periodontitis formation.The results of biochemical studies showed that at all stages of the development of experimental periodontitis, there is a consistent increase in the degree of endogenous intoxication with their dominance on the 15 th  day of the experiment relative to the control, namely, the content of medium-mass molecules (МMМ254, МMМ280) and the erythrocyte intoxication index (EII) increased in blood, respectively, by 24.8% (р≤0.05), 28.2% (р≤0.05) and 34.7% (р≤0.05) compared to the first group of animals, which indicates an increase in the processes and the important role of metabolites of endogenous intoxication and their participation in the mechanisms of formation of experimental periodontitis.